Universality, factionalism and exclusion. Representative democracy and populist democracy in the work of Nadia Urbinati (Res Publica. Revista de Historia de las Ideas Políticas, 2024)
The political scientist Nadia Urbinati claims that populism is not an anti-democratic movement. Nevertheless, she establishes a contrast between "representative democracy" and "populist" democracy”. The logic proper to the former would be synecdochic (pars pro toto), while the latter would involve a factional logic (pars pro parte). Starting from her definition of representative democracy and by contrasting it with Ernesto Laclau and Chantal Mouffe’s theory of populism, it will be argued that, far from representing a "disfigurement" of the fundamental democratic principles, populism is built upon the same representative matrix (in which synecdoche plays a central role). It also operates with mechanisms of exclusion shared by the rest of democratic movements.